Assessing the sustainability of seal tourism at Duiker Island, Hout Bay - Heide, Trygve (Department of Biological Sciences, 2021)
Pinniped focused tourism has grown rapidly both globally and in South Africa. In a 2002 survey South Africa was identified as having earned the most revenue from seal ecotourism of all the countries that engage in this activity. Seal tourism includes approaching colonies on foot, by kayak, on large and small motorised boats and more recently in the water through snorkelling and scuba diving activities. Like most wildlife tourism seal snorkelling operators can use their tours to educate clients about seal biology and threats, while providing them with a memorable physical experience with minimal impact on the seals. The goal of this research was to explore aspects of the demography, attitudes and values of tourists participating in two different seal viewing activities at the same island. Additionally, I investigated levels of satisfaction with each tour type, differences in the style of education provided by operators and which tour provided tourists and what facts tourists found most interesting. In the second part of the study I quantified the behavioural response of seals to tourists who entered the water to snorkel with seals in an attempt to assess potential impacts of immersive trips on seal behaviour. The study was conducted at Duiker Island, near Hout Bay in the city of Cape Town between November 2019 and January 2020. This period coincides with the breeding season of Cape fur seals (Arctocephalus pusillus pusillus) and the peak tourist season. Questionnaires were distributed to both seal viewing tourists (n = 53) who had viewed seals from a large boat and seal snorkelling participants who had swum with seals at the island (n = 90). More women than men undertook both types of tour, though the proportion of men increased on snorkelling compared to viewing tours. Probit models revealed key behavioural and attitudinal differences between seal viewing and seal snorkelling participants with the latter being more pro-environmental. Seal snorkelling guides used a more interpretive style when educating tourists including the use of visual aids while seal viewing tours announced facts through a loudspeaker on the vessel. Seal snorkelling guides would also include information to awareness about plastic pollution and seal entanglement, with a donation box for a seal disentanglement program run by the Two Oceans Aquarium. Seal snorkelling participants listed an average of two facts they had learnt on the tour compared to a mean of 1.24 facts for seal viewing tours. Both tours were rated very highly for overall levels of satisfaction (seal snorkelling mean score = 9.17/10; seal viewing = 8.58/100). Surface observations of seal behaviour in response to seal snorkelers in the water close to the boat suggested a minimal impact with most seals (88%) behaving neutrally and only 0.2 % engaged in avoidance behaviour. Below water observations revealed that seal numbers declined with increasing number of people in the water and seals adjusted both their position in the water column (more diving) and their activity (more active) in response to snorkeler presence. These findings suggest that both the number of snorkelers and the area over which they spread should be controlled so that seals can choose to avoid snorkelers and behavioural changes are localised to select demarcated areas. The presence of the guides in the water together with the tourists ensured there were no inappropriate interactions between seals and snorkelers (e.g. touching and biting by seals in response). This is the first study on the thriving seal ecotourism industry at Duiker Island and reveals high levels of satisfaction by both seal viewing and seal snorkelling tourists. While there were measurable impacts of seal snorkelers on seals these were highly localised and unlikely to present an adverse impact on seals at the Island more generally. Controlling the number of operators and ensuring snorkelers are always accompanied by guides should ensure that this valuable business continues, potential impacts are minimised and negative interactions (e,g. bites from seals or people touching or feeding seals) are prevented.